Abstract 136: Antiplatelet Regimens for Secondary Prevention in Minor Ischemic Stroke or TIA: A Network Meta‐Analysis - Hesham Kelani (Stroke: Vascular and Interventional Neurology)
Introduction There is increased risk of major cardiovascular events among patients with minor ischemic stroke or transient ischemic attack (TIA) [1]. Antiplatelet drugs have been proven to reduce the risk of major cardiovascular events and highly recommended for secondary stroke prevention in this population [2]. However, using antiplatelets has shown an increase in the risk of bleeding events. Hence there are multiple antiplatelet regimens, we aim to investigate the efficacy and safety of these different regimens in minor ischemic stroke defined as National Institutes of Health Stroke Scale (NIHSS) score of 5 or less and high‐ risk TIA). Methods A comprehensive literature search of (PubMed, Cochrane, Scopus, and WOS) was conducted to identify randomized controlled trials comparing different antiplatelet regimens in patients with minor ischemic stroke or TIA. Frequentist NMA was conducted to estimate relative risks (RR) and 95% confidence intervals (CI) for the outcomes of interest using R statistical programming language [3]. The primary outcome measure was recurrent stroke while secondary outcomes included, any bleeding events, serious adverse events (SAEs), hemorrhagic stroke, myocardial infarction (MI), cardiovascular mortality, and all‐cause mortality. Results Five RCTs with 34,941 participants were included. Compared to SAPT (aspirin alone), both DAPT regimens (aspirin + clopidogrel and aspirin + ticagrelor) demonstrated a significant reduction in stroke recurrence (RR: 0.72 with 95% CI [0.63, 0.82], P < 0.01) and (RR: 0.75 with 95% CI [0.64, 0.87], P < 0.01), respectively. However, both DAPT regimens were associated with a higher risk of bleeding events (RR: 1.95 with 95% CI [1.09, 3.50], P = 0.02), (RR: 3.07 with 95% CI [1.16, 8.15], P = 0.02), respectively. In contrast, no significant differences were observed among various antiplatelet modalities regarding all‐cause mortality, cardiovascular mortality, hemorrhagic stroke, myocardial infarction, and serious adverse events. In contrast, no significant differences were observed among various antiplatelet modalities regarding all‐cause mortality, cardiovascular mortality, hemorrhagic stroke, myocardial infarction, and serious adverse events. Conclusion Our findings indicate that DAPT regimens were effective in reducing stroke recurrence compared to SAPT. However, caution is warranted as both DAPT regimens were associated with a higher risk of bleeding events. Clinicians should weigh the potential benefits of reduced stroke recurrence with DAPT against the increased risk of bleeding events. Further research and clinical trials assessing both safety and efficacy are warranted to better understand the optimal prevention approach for this specific patient population.